Butterflies and moths - Feltwell, John. (New York : Dorling Kindersley, 1993)
Explains how to watch and understand the world of butterflies and moths.
Eyes and seeing -- Smelling and sipping -- Looking at legs -- All about eggs -- Caterpillar birth -- Feeding machines -- Changing skin -- Silk cocoons -- In the woodlands -- In the mountains -- In the rainforest -- In the desert -- In the arctic.
Wilson's Children
Child Study Children's Book Committee
Horn Book
5.3
3-6
Keywords: Moths -- Juvenile literature; Butterflies -- Juvenile literature; Moths; Butterflies; Moths; Butterflies